REFLECTIVE TEACHING TO IMPROVE NOVICE TEACHER'S PERFORMANCE : Classroom Action Research in a Private Islamic Vocational Boarding School in Cianjur - Martina, Feny (2013)
The first years of teaching career have been indisputably problematic for most of novice teachers. Not only possessing the new environment of the work place to adapt to, but also handling and maintaining adequate classroom performances are of the major issues, which in turn, some helps are assumed crucial for them. Considering the importance to overcome the matters, this study was aimed at investigating reflective teaching (RT) undertaken by a novice teacher in an attempt to improve his classroom performances. This is classroom action research (CAR), where the practice of RT was undertaken through collaborative mentoring. The novice teacher, in this case, had a joint-work with an experienced teacher. The novice teacher acted as a teacher mentee and the experienced one as the teacher mentor. In addition, this study was also aimed at acquiring opinions from both teacher mentee and teacher mentor about the implemented RT. The data were collected through questionnaires, observations, interviews & triadic and/or dyadic conferences, and document collections. They were analyzed both quantitatively and qualitatively. As the results, through the process of RT, the teacher mentee's improved performances were identified. However, the improvement was seen only from the aspects of teacher pedagogical knowledge, and not yet explored from the aspects of the teacher content knowledge. This indicated that another further study of RT viewed from the related observed aspects of teacher content knowledge seems necessarily demanding. Keywords: Reflective teaching (RT), mentoring, novice teacher, pedagogical content knowledge